2020
DOI: 10.1021/acs.nanolett.0c00258
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Tunable Interlayer Exciton Emission at the Near-Infrared Region in van der Waals Semiconductor Heterostructures

Abstract: The wavelength-tunable interlayer exciton (IE) from layered semiconductor materials has not been achieved. van der Waals heterobilayers constructed using single-layer transition metal dichalcogenides can produce continuously changed interlayer band gaps, which is a feasible approach to achieve tunable IEs. In this work, we design a series of van der Waals heterostructures composed of a WSe2 layer with a fixed band gap and another WS2(1–x)Se2x alloy layer with continuously changed band gaps. The existence of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…2c-e), which was attributed to the twist-angle dependence of the interlayer coupling strength in these heterostructures. In addition, it was reported that the PL energy of interlayer excitons could be tuned by many other factors such as the vdW bandgap 90 , electric and magnetic fields 22,[108][109][110] , cavity [111][112][113] , pressure 114 , and layer number 115 . Moreover, even electroluminescence (EL) from interlayer excitons was observed in TMD vdW heterobilayers under a forward bias 30,32,102 .…”
Section: Interlayer Exciton Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…2c-e), which was attributed to the twist-angle dependence of the interlayer coupling strength in these heterostructures. In addition, it was reported that the PL energy of interlayer excitons could be tuned by many other factors such as the vdW bandgap 90 , electric and magnetic fields 22,[108][109][110] , cavity [111][112][113] , pressure 114 , and layer number 115 . Moreover, even electroluminescence (EL) from interlayer excitons was observed in TMD vdW heterobilayers under a forward bias 30,32,102 .…”
Section: Interlayer Exciton Formationmentioning
confidence: 99%
“…In addition, the spatial separation between charges creates a permanent electrical dipole moment in the out-of-plane direction, which allows electrical control of their optical and transport properties along with the generation of repulsive dipole-dipole interactions between them 22,[28][29][30] . All these features make interlayer excitons an appealing platform for exploring many-body effects, such as Bose-Einstein condensation (BEC) and superfluidity 31,32 and highly desirable for developing potential excitonic The experimental PL energies of the interlayer excitons (stars in the pink region) are obtained from references 17,[21][22][23]25,[27][28][29]33,[42][43][44][45]49,87,[90][91][92][93][94][95][96][97][98][99][100][101][102][103] , most of which overlap in the region from~1.3 to~1.5 eV. d Band alignment of a MoS 2 /WS 2 heterobilayer 57 .…”
Section: Introductionmentioning
confidence: 99%
“…This bandgap bowing effect can be explained by the different lowest unoccupied molecular orbital (LUMO) compositions and energies between MoS2 and WS2, and then LUMO bowing occurs [24]. Additionally, alloy heterostructure could bring interesting properties, e.g., wavelengthtunable (816.0 to 886.0 nm) interlayer excitons have been obtained from WSe2/WS2(1−x) Se2x (0 ≤ x ≤ 1) van der Waals heterobilayer [102].…”
Section: Tunable Bandgap From Alloysmentioning
confidence: 99%
“…Band alignment engineering at the interface of 2D heterostructures is an efficient way to tailor the related optical and electronic properties, which is crucial for the designing of functional electronic and optoelectronic devices. There are many modulation approaches to modulate the band alignment in heterostructures, such as from the perspective of semiconductors composition, [ 108–110 ] components thickness, [ 72,96 ] applying strain, [ 25,26,111,112 ] or electric field. [ 100,106,107 ] Here, we mainly introduce three approaches of them and declare the variation in the related properties as well as the derived functions.…”
Section: Band Alignment Engineeringmentioning
confidence: 99%
“…Through tuning the x in WS 2(1− x ) Se 2 x heterostructures, Li et al. realized the successful tuning of the emission energy of ILEs from 1.52 to 1.40 eV (Figure 2b), [ 108 ] which can be potentially used in wavelength‐tunable LEDs.…”
Section: Band Alignment Engineeringmentioning
confidence: 99%